6x+36=-3(x+9)

Simple and best practice solution for 6x+36=-3(x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+36=-3(x+9) equation:



6x+36=-3(x+9)
We move all terms to the left:
6x+36-(-3(x+9))=0
We calculate terms in parentheses: -(-3(x+9)), so:
-3(x+9)
We multiply parentheses
-3x-27
Back to the equation:
-(-3x-27)
We get rid of parentheses
6x+3x+27+36=0
We add all the numbers together, and all the variables
9x+63=0
We move all terms containing x to the left, all other terms to the right
9x=-63
x=-63/9
x=-7

You can always share this solution

See similar equations:

| -6(u-2)=-8u+14 | | 2w+9=9(w+8) | | 30-5z=8(9z+7) | | C/4+76=4b | | 4x+9x-8x=6+4 | | 8x-90=-2 | | 6+1/2x=x(2) | | 3/2a+1/4=5/8 | | v^2+15v+59=0 | | 5y×2y=-24 | | 3-x/5=10 | | -4(w-9)=3w+8 | | -9y+20=-2(y-3) | | 5(x+2)=6x+3x-14 | | -3(y+4)=5y-28 | | 10k(k+2)=k-6 | | -45b=-39b | | d+12/6=20/8 | | F(t)=1,500(1.045) | | j*7=56 | | v*7=28 | | 7*v=48 | | v*7=48 | | 2*i=18 | | c*5=35 | | 4a+a=20;a= | | 1/4-10=7;b= | | 1/3(x+8)=10 | | 2x+25=32 | | 7w-38=-4(w-7) | | v2=-84 |

Equations solver categories